2013
DOI: 10.1155/2013/373240
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Teacher-Report Assessments of Autistic Severity in Japanese School Children

Abstract: Recent studies suggest that many children with milder autism spectrum disorder (ASD) are undiagnosed, untreated, and being educated in mainstream classes without support and that school teachers might be the best persons to identify a child's social deviance. At present, only a few screening measures using teacher ratings of ASD have been validated. The aim of this study was to examine the utility of teacher ratings on the Social Responsiveness Scale (SRS), a quantitative measure of ASD. We recruited 130 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…These studies cannot be easily compared because the age ranges studied in their samples were not identical. However, the tendency for Japanese parents or teachers to give lower scores to children’s behaviors appears consistent among questionnaires such as the CBCL [29], ADHD-RS [33,34], and Social Responsiveness Scale [40,41]. One partial explanation for the relatively lower scores of Japanese children on behavioral measures such as the SDQ is that Japanese informants tend to respond to Likert-type ratings by choosing the scale’s midpoint, whereas U.S. informants tend to choose the scale’s extreme values [42].…”
Section: Discussionmentioning
confidence: 94%
“…These studies cannot be easily compared because the age ranges studied in their samples were not identical. However, the tendency for Japanese parents or teachers to give lower scores to children’s behaviors appears consistent among questionnaires such as the CBCL [29], ADHD-RS [33,34], and Social Responsiveness Scale [40,41]. One partial explanation for the relatively lower scores of Japanese children on behavioral measures such as the SDQ is that Japanese informants tend to respond to Likert-type ratings by choosing the scale’s midpoint, whereas U.S. informants tend to choose the scale’s extreme values [42].…”
Section: Discussionmentioning
confidence: 94%
“…Szatmari et al (1994) found differences between parent and teacher reports of autism severity for the same child, with teachers regularly reporting lower levels of difficulty than parents. Other studies indicate that teachers are likely to rate FwASD as having fewer observable difficulties in school than MwASD (Kamio et al 2013;Mandy et al 2012). Observable autism severity may be context-dependent (Posserud et al 2006) and FwASD may particularly benefit from the structured environment of school, thus reducing externalising behaviours (Szatmari et al 1994).…”
Section: Report Measures For Females With Asd: Implications For Pragmmentioning
confidence: 99%
“…By increasing the cut‐off scores to 89.5 for the parent form, and to 70.0 for the teacher form, the specificity increased to 0.92 for parent scores, and 0.83 for teacher scores. Among a mixed Japanese sample that included ASD, non‐ASD clinical and typical developing children, a parent‐rated score of 53.5 for boys and 52.5 for girls was suggested as being optimal for the purpose of primary screening for case referral and 109.5 for boys and 102.5 for girls for the purpose of secondary screening for diagnostic classification [Kamio, Inada, et al, ], while teacher‐rated scores of 58.0 for boys (sensitivity 0.725, specificity 0.667) and 43.0 for girls (sensitivity 0.789, specificity 0.667) were judged as being optimal screening cut‐off scores [Kamio, Moriwaki, & Inada, ]. These previous studies have shown that the SRS can be regarded as a valid screening tool across different cultural settings, although purpose‐specific cut‐off scores need to be chosen.…”
Section: Introductionmentioning
confidence: 99%